Study of the inclusive production of charged pions, kaons, and protons in pp collisions at √s = 0.9,2.76 and 7 TeV - Chatrchyan, S; Chatrchyan, S; Khachatryan, V; Khachatryan, V; Sirunyan, A; Sirunyan, A; Tumasyan, A; Tumasyan, A; Adam, W; Adam, W; Aguilo, E; Aguilo, E; et al. (2012)
Spectra of identified charged hadrons are measured in pp collisions at the LHC for √s = 0.9,2.76, and 7 TeV. Charged pions, kaons, and protons in the transverse-momentum range p T≈0. 1-1. 7 GeV/c and for rapidities pipeypipe<1 are identified via their energy loss in the CMS silicon tracker. The average p T increases rapidly with the mass of the hadron and the event charged-particle multiplicity, independently of the center-of-mass energy. The fully corrected p T spectra and integrated yields are compared to various tunes of the Pythia 6 and Pythia 8 event generators. © 2012 CERN for the benefit of the CMS collaboration.